Evaluasi Kapasitas Pondasi Tiang Pancang Menggunakan Data Kalendering Pada ABT1-ABT 2 Underpass STA 2+550 Binjai-Stabat - Darlina Tanjung; Jupriah Sarifah; Vikhri Haichal Rambe (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
A pile foundation is needed to support the building, if the hard soil layer is very deep. The pile foundation functions to move or transfer the load above it (superstructure) to deeper soil layers. For this purpose, it is necessary to evaluate the capacity of a single pile and the capacity of a group of piles that are capable of carrying the load above them. Evaluation of pile capacity requires calendaring data in the form of field driving data which is carried out when the pile reaches hard ground with penetration and rebound values taken for 10 strokes. Based on calendaring data, single pole capacity analysis was carried out using several methods. The results of the bearing capacity analysis from one method are compared with other methods and their relationship with pile penetration. The capacity value of the pile group is calculated based on the pile efficiency. Most of the pile capacities show almost the same single pile capacity values, such as the Hiley method (666.16 kN), Navy-Mckay (752.14 kN), Janbu (440.91 kN), except that the Sanders method gives results that are much different from The value of other methods is 1138.28 kN, this could be because this method only considers the weight of the pile. The relationship between single pile capacity and pile penetration shows that the smaller the pile penetration value, the greater the pile capacity. This is obtained in all methods used, although with different calculation methods and method.